2023
DOI: 10.1021/acs.jcim.2c01494
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Calcium Permeation in a Glutamate Receptor Ion Channel

Abstract: The α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptors (AMPARs) are neurotransmitter-activated cation channels ubiquitously expressed in vertebrate brains. The regulation of calcium flux through the channel pore by RNA-editing is linked to synaptic plasticity while excessive calcium influx poses a risk for neurodegeneration. Unfortunately, the molecular mechanisms underlying this key process are mostly unknown. Here, we investigated calcium conduction in calcium-permeable AMPAR using Molecular Dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…Within this condition, the carboxylic groups of aspartic acids are saturated by calcium ions, and new ions injected in the pore push an internal calcium ion to exit, reminding the knock-off mechanism also proposed very recently for other calcium channels ( Schackert et al, 2023 ). In particular, the residue at position P2 has the highest residence time for calcium, providing a bridge between position P1 and P3, Figure 5 .…”
Section: Discussionmentioning
confidence: 60%
“…Within this condition, the carboxylic groups of aspartic acids are saturated by calcium ions, and new ions injected in the pore push an internal calcium ion to exit, reminding the knock-off mechanism also proposed very recently for other calcium channels ( Schackert et al, 2023 ). In particular, the residue at position P2 has the highest residence time for calcium, providing a bridge between position P1 and P3, Figure 5 .…”
Section: Discussionmentioning
confidence: 60%
“…A potential of 10 mV Å –1 was set. Not too dissimilar potentials have been used in other setups, such as the computational electrophysiology simulations. Here, 3 μs were simulated with and without the electric field, using a simpler one-dimensional CV space (see Figure S14a in Supporting Information).…”
Section: Methodsmentioning
confidence: 99%
“…The CHARMM36m force field was used for the protein, ions other than Ca 2+ , and the lipids [36] . For the Ca 2+ ions, the multi-site model developed by Zhang et al was used, which has recently been shown by us and other groups to reliably model Ca 2+ currents in a range of ion channels [37][38][39][40][41] Hydrogen mass re-partitioning (HMR) of the system was used in the simulations with Na + ions such that 4-fs time steps could be employed [42] . However, 4-fs time steps are incompatible with the multi-site Ca 2+ model, and consequently, a standard 2-fs time step was used in all simulations with Ca 2+ , retaining HMR for consistency.…”
Section: Methodsmentioning
confidence: 99%